The risk of developing alcohol addiction - what coping strategies do Ukrainian military personnel use after participating in intense hostilities? - Prykhodko, Ihor; Matsehora, Yanina; Baida, Maksim; Zahrebelnyi, Oleksandr; Lipatov, Ivan; Kuzina , Viktoriia; Marushchenko, Kateryna; Rumiantsev, Yurii; Skliarova, Hanna; Склярова, Ганна Олександрівна (Publishing Office of the University of Rzeszow, 2024)
Introduction and aim. Since February 24, 2022, military personnel of the Ukrainian Defense Forces have been resisting the military aggression of the Russian Federation. After participating in combat operations, military personnel accumulated combat stress. Drinking alcohol was one of the ways to overcome it. The purpose of the article is to identify the types of coping strategies for the risk of developing alcohol addiction among Ukrainian military personnel who participated in intense hostilities. Material and methods. Ukrainian Defense Forces military personnel (n=162 males, between 20 and 60 years of age) took part in this study. To determine coping strategies and the risk of developing alcohol addiction the AUDIT and the COPE Inventory were used. Results. Cluster analysis made it possible to identify 4 types of coping strategies with different prevalence and levels of risk of developing alcohol addiction among participants. Conclusion. Productive coping has been associated with a reduced risk of alcohol use in military personnel, but the ability to be situational flexible in the use of coping is important. Compulsive alcohol use was preceded by a period of intensive use of social support coping by military personnel. This period is sensitive to the risk of developing alcohol addiction.
Keywords: alcohol addiction; coping strategies; military personnel